2021
DOI: 10.3390/cancers13215258
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs Correlate with Multiple Myeloma and Skeletal Osteolytic Lesions

Abstract: Multiple myeloma (MM) is the second most frequent hematological disease and can cause skeletal osteolytic lesions. This study aims to evaluate the expression of circulating microRNAs (miRNAs) in MM patients and to correlate those levels with clinicopathological features, including bone lesions. A panel of miRNAs associated with MM onset and progression, or with bone remodeling, was analyzed in the plasma of 82 subjects (47 MM patients; 35 healthy controls). Results show that miR-16-5p, miR-20a-5p, and miR-21-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Furthermore, we showed that the H19 expression is regulated by miR-29c-3p, whose levels are decreased in bone samples from osteoporotic patients, and that it negatively changes COL1 expression, which is in agreement with previous studies [59,60]. In a recent study published by our group, miR-29c-3p was identified as a marker of secondary osteoporosis in multiple myeloma plasma samples [61]. Modulation of miR-29c-3p affects MSC proliferative capacity, without impacting cell death or osteogenic differentiation and mineralization in the early stages of differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we showed that the H19 expression is regulated by miR-29c-3p, whose levels are decreased in bone samples from osteoporotic patients, and that it negatively changes COL1 expression, which is in agreement with previous studies [59,60]. In a recent study published by our group, miR-29c-3p was identified as a marker of secondary osteoporosis in multiple myeloma plasma samples [61]. Modulation of miR-29c-3p affects MSC proliferative capacity, without impacting cell death or osteogenic differentiation and mineralization in the early stages of differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…miR-21 serum levels at relapse were associated with ISS stage. From previous studies, plasma levels of miRNA 16 were associated with B2M [ 24 ], ISS disease stage and PFS in myeloma [ 18 ]. In addition, serum miR-21 was significantly different according to the Durie and Salmon stages, correlating with B2M, IgG, and albumin levels [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Also, we showed H19 expression is regulated by miR-29c-3p, which levels are decreased in bone samples from osteoporotic patients, and that negatively changes COL I expression, which is in agreement with previous studies 49,50 . In a recent study published by our group, miR-29c-3p was identi ed as a marker of secondary osteoporosis in multiple myeloma plasma samples 51 . Modulation of miR-29c-3p affects MSC proliferative capacity, without changing cell death or osteogenic differentiation and mineralization in early stages of differentiation.…”
Section: Discussionmentioning
confidence: 99%